Presentation to healthcare and the prevalence of frailty among older adults to the outpatient department of a tertiary care hospital in Sri Lanka - M. M. P. T. Jayasekera; C. D. K. Hulugalla; S. M. Ramawickrama; A. P. Merusinghe; T. D. Marasinghe; E. M. D. T. Edirisinghe (Sri Lanka College of Internal Medicine, 2023)
Background: Sri Lanka is one of the fastest-ageing countries in the world, with the proportion of the population aged 60 years or older projected to increase from 12.5% in 2016 to 16.7% in 2021. By 2041, one out of every four individuals in Sri Lanka is expected to be an elderly person. In this study, the burden of geriatric presentation to a hospital's outpatient department (OPD) was assessed. These patients' frailty, along with comorbidities, the existing level of geriatric care by the healthcare team at the OPD, and the level of patient satisfaction were also studied. Methods: A cross sectional study was conducted in March 2021. Results: Of 406 recruits 58.4% were female and their mean (+SD) age was 72.25 (+5.63) years. Among them, 39.7% (95% CI 34.9% to 44.6%) were frail. There was a higher prevalence of frailty among men than women (p=.001). Hypertension was the most common comorbidity. The most common diagnosis was musculoskeletal pain followed by leg ulcers. The mean consultation time with waiting time was 56 (+54 SD) minutes. Most patients classified their overall feeling of satisfaction as "good" (80.3%) while 5% stated it was poor. Conclusions: The prevalence of frailty among this sub-urban population is higher than previous studies. A majority of patients presented with non-life-threatening conditions and classified their overall satisfaction as relatively good.